CO2 laser polishing of microfluidic channels fabricated by femtosecond laser assisted carving. (5th October 2016) - Serhatlioglu, Murat; Ortaç, Bülend; Elbuken, Caglar; Biyikli, Necmi; Solmaz, Mehmet E
Abstract: In this study, we investigate the effects of CO2 laser polishing on microscopic structures fabricated by femtosecond laser assisted carving (FLAC). FLAC is the peripheral laser irradiation of 2.5D structures suitable for low repetition rate lasers and is first used to define the microwell structures in fused silica followed by chemical etching. Subsequently, the bottom surface of patterned microwells is irradiated with a pulsed CO2 laser. The surfaces were characterized using an atomic force microscope (AFM) and scanning electron microscope (SEM) in terms of roughness and high quality optical imaging before and after the CO2 laser treatment. The AFM measurements show that the surface roughness improves more than threefold after CO2 laser polishing, which promises good channel quality for applications that require optical imaging. In order to demonstrate the ability of this method to produce low surface roughness systems, we have fabricated a microfluidic channel. The channel is filled with polystyrene bead-laden fluid and imaged with transmission mode microscopy. The high quality optical images prove CO2 laser processing as a practical method to reduce the surface roughness of microfluidic channels fabricated by femtosecond laser irradiation. We further compared the traditional and laser-based glass micromachining approaches, which includes FLAC followed by the CO2 polishing technique.